ANALISIS BIAYA OPERASIONAL DAN ARUS KAS TERHADAP PROFITABILITAS PADAPT. JASA RAHARJA (PERSERO) CABANG MANADO - Marianti Jela-Jela; Tinneke Tumbel; Henny Tarore (JURNAL ADMINISTRASI BISNIS, 2016)
ABSTRACT : Umploying kash operational and management cash flow operatio ini finance operational activity exaration be influence attachment company profitability. The objective research this script is to know how the as much as cash operation and cash flow operation involve the us of inflonce profitability on PT. Jasa Raharja (Persero) Branch Manado.The Method research is desckriptive method and approach quantitative use Analysis of Financial report, Procesing and procesing source in from PT. Jasa Raharja (Persero) Branch Manado. And outcome level’s operation cash in use by PT. Jasa Rahrja (Persero) Branch Manado, Starting at or from the year 2013 to 2015 in the amount of is Rp. 757.097.256.00, Level’s cash low the year 2103 To 2015 in the amount of is Rp. 20.198.954.033.00,Perfomnce Ratio Profitability On PT. Jasa Rahrja (Persero) Branch Manado., Break the year 2013 To 2015 PT. Jasa Rahrja (Persero) Branch Manado. Level’s Net Profit Margin : 0,379, Level’s Return On Asset :4,343, Level’s Profit Margin : 0,62. Proposition in onder to PT. Jasa Raharja (Persero) Branch Mando,Always interest to management opereational cash in to ectivity operational Work until Perfomnce target profitability Work corporation talked about can realization befit pleaning, The Proposition in onder to PT. Jasa Raharja (Persero) Branch Mando, Always interst performance Official fot the sake of Effectveness and Effecincy PT. Jasa Raharja (Persero) Branch Mando Sulawesi Utara, until Able Keep Reputation as foault Corporation Work Community Responsibility the Predominance and Beliveble.Keywords : ( Operational Cash, Cash Flow Operation, Profitability)